An Interactive Learning Network That Maintains Sentiment Consistency in End-to-End Aspect-Based Sentiment Analysis - Musheng Chen; Qingrong Hua; Yaojun Mao; Junhua Wu (Applied Sciences, 2023)
Most of the aspect-based sentiment analysis research completes the two subtasks (aspect terms extraction and aspect sentiment classification) separately, and it cannot see the full picture and actual effect of the complete aspect-based sentiment analysis. The purpose of end-to-end aspect-based sentiment analysis is to complete the two subtasks of aspect terms extraction and aspect sentiment classification at the same time, and the current research in this area focuses on the connection between the two subtasks and uses the connection between them to construct the model. However, they rarely pay attention to the connection between different aspects and ignore the sentiment inconsistency within the aspects caused by the end-to-end model. Therefore, we propose an interactive learning network to maintain sentiment consistency, first using the multi-head attention mechanism to achieve the interaction between aspects and subtasks and then using the gate mechanism to design an auxiliary module to maintain sentiment consistency within aspect items. The experimental results on the datasets Laptop14, Restaurant14, and Twitter showed that, compared with the optimal benchmark method, the F1 values of the proposed method increased by 0.4%, 1.21%, and 5.22%, respectively. This indicates that the proposed method can effectively consider the relationships between aspect items and maintain emotional consistency within the aspect items.